ROLE OF COUNSELLING IN PROMOTING VOCATIONAL SKILLS DEVELOPMENT AMONG STUDENTS IN FUNCTIONAL EDUCATION FRAMEWORKS - MAIKAMBA, Abubakar, M.; N. ISA, Aisha; AMINU, Mohammed, J.; YAUTA, Aminu, M. (Journal of Professional Counselling, 2025)
In today’s rapidly changing global economy, vocational skills development has become critical for students to succeed in the workforce. Functional education frameworks, which emphasize practical and applied learning, are increasingly being adopted to prepare students for realworld challenges. Counselling plays a pivotal role in promoting vocational skills development within these frameworks by providing students with the guidance, support, and resources necessary to make informed decisions about their career paths. This paper explores the role of counselling in vocational skills development, focusing on how counselling interventions can enhance students' readiness for the workforce and contribute to their overall personal and professional growth.